Augmented BH4 by gene transfer restores nitric oxide synthase function in hyperglycemic human endothelial cells. - Cai, S; Khoo, J; Channon, K (2005)
OBJECTIVE: Endothelial dysfunction in diabetes is characterized by decreased nitric oxide (NO) bioactivity and increased superoxide (SO) production. Reduced levels of tetrahydrobiopterin (BH4), an essential cofactor of endothelial NO synthase (eNOS), appear to be associated with eNOS enzymatic uncoupling. We sought to investigate whether augmented BH4 biosynthesis in hyperglycemic human aortic endothelial cells (HAEC) by adenovirus-mediated gene transfer of GTP cyclohydrolase I (GTPCH, the rate-limiting enzyme for the de novo BH4 synthesis), would be sufficient to rescue eNOS activity and dimerization. HAEC were cultured in media with low glucose (5 mM) or high glucose (30 mM). METHODS: After 5 days, the cells with/without GTPCH gene transfer (AdeGFP as a control) were prepared for assays of (1) NO with electron paramagnetic resonance (EPR); (2) SO with cytochrome c reduction and dihydroethidine (DHE) fluorescence; (3) BH4 with high-performance liquid chromatography (HPLC); (4) eNOS expression and dimerization with immunoblotting. RESULTS: We found that high glucose decreased HAEC NO and increased SO production, in association with reductions in both total biopterin and BH4 levels. High glucose increased total eNOS protein levels in HAEC 1.5-fold, but this was present principally in the monomeric form. GTPCH gene transfer increased cellular biopterin levels and NO production but decreased SO production. Furthermore, augmenting BH4 increased the eNOS dimer:monomer ratio 2.6-fold. CONCLUSION: This study demonstrates a critical role for BH4 in regulating eNOS function, suggesting that GTPCH is a rational target to augment endothelial BH4 and recover eNOS activity in hyperglycemic endothelial dysfunction states.